2016
DOI: 10.21101/cejph.a4872
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials - a New and Former Public Health Issue. The Case of Slovakia

Abstract: SUMMARYNanoparticles exist for a long time as both inorganic and organic parts of nature. Recently, massive expansion of nanotechnologies is evidenced, together with intentional production of new nanoparticles which have not been in contact with living organisms until now. Besides obvious positive aspects, potential threats related to their exposure should be taken into consideration. Unique physical-chemical properties of nanoparticles cause a high bioactivity following their intake (through air, ingestion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…These sequential molecular and cellular events are known to cause oxidative stress, followed by severe cellular genotoxicity and then programmed cell death. Both experimental and epidemiological studies have indicated that chronic inflammation is involved in and plays a critical role in several chronic diseases, including respiratory and cardiovascular diseases, and lung tumorigenesis [ 17 , 19 , 20 , 21 ]. However, there is no evidence that particles below 100 nm show any step-change in their hazard meaning that there is no evidence of any novel “nano-specific hazard”.…”
Section: Introductionmentioning
confidence: 99%
“…These sequential molecular and cellular events are known to cause oxidative stress, followed by severe cellular genotoxicity and then programmed cell death. Both experimental and epidemiological studies have indicated that chronic inflammation is involved in and plays a critical role in several chronic diseases, including respiratory and cardiovascular diseases, and lung tumorigenesis [ 17 , 19 , 20 , 21 ]. However, there is no evidence that particles below 100 nm show any step-change in their hazard meaning that there is no evidence of any novel “nano-specific hazard”.…”
Section: Introductionmentioning
confidence: 99%
“…Solid carbon-13 NMR data was acquired using a VNMRS 400 widebore spectrometer operating at 399.9 MHz for 1 H and 100.5 MHz for 13 C in a 4 mm Varian Chemagnetics double-resonance probe.…”
Section: Solid-state Carbon-13 Nmrmentioning
confidence: 99%
“…The 1 H spectra (500 MHz, D2O) were acquired using a Varian VNMRS using a switchable broadband probe. 3000 scans were used for the 13 C spectrum and 16 for the proton,…”
Section: Liquid-state Hydrogen and Carbon-13 Nmrmentioning
confidence: 99%
“…The European Commission defines nanomaterial as a natural, incidental or manufactured material containing particles in an unbound state or as an aggregate or agglomerate and where, generally for 50% or more of the particles in the number size distribution, one or more external dimensions range from 1-100 nm in size. They can be spherical, tubular, or irregularly shaped and can exist in fused, aggregated or agglomerated forms (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%